2009
DOI: 10.1186/1471-2407-9-87
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of UbcH10 alternates the cell cycle profile and accelerate the tumor proliferation in colon cancer

Abstract: BackgroundUbcH10 participates in proper metaphase to anaphase transition, and abrogation of UbcH10 results in the premature separation of sister chromatids. To assess the potential role of UbcH10 in colon cancer progression, we analyzed the clinicopathological relevance of UbcH10 in colon cancer.MethodsWe firstly screened the expression profile of UbcH10 in various types of cancer tissues as well as cell lines. Thereafter, using the colon cancer cells line, we manipulated the expression of UbcH10 and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 38 publications
(55 reference statements)
7
69
0
Order By: Relevance
“…Our study demonstrated that siRNA-mediated suppression of UBE2C expression inhibited the growth rate of CRC cells with accumulation of cyclins A and B1, which was consistent with earlier reports. 13,16 Interestingly, we found that down-regulation of UBE2C expression caused inhibition of cell viability by arresting cells in the G2/M phase followed by induction of apoptosis in CRC cells. UBE2C expression in CRC cell lines was found to be inversely associated with cyclin A and B1 in concordance with the mechanistic model of UBE2C function.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Our study demonstrated that siRNA-mediated suppression of UBE2C expression inhibited the growth rate of CRC cells with accumulation of cyclins A and B1, which was consistent with earlier reports. 13,16 Interestingly, we found that down-regulation of UBE2C expression caused inhibition of cell viability by arresting cells in the G2/M phase followed by induction of apoptosis in CRC cells. UBE2C expression in CRC cell lines was found to be inversely associated with cyclin A and B1 in concordance with the mechanistic model of UBE2C function.…”
Section: Discussionmentioning
confidence: 87%
“…This is in agreement with earlier studies in which UBE2C expression was significantly higher in a wide variety of cancer from colon, esophagus, ovary, breast, and lung compared with their healthy counterparts. 12, 16 Lin et al 10 demonstrated a higher expression of UBE2C at the protein and mRNA levels in esophageal carcinoma and dysplastic lesions compared with metaplastic lesions. In concordance with earlier studies, UBE2C gene amplification was associated with distant metastasis (pM1), 15 and UBE2C alteration was significantly associated with Ki-67 (a proliferative marker), accumulation of cyclin A and B1, and a poor overall survival.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, regulation of UbcH10 expression might also be an essential step for proper function of the checkpoint. Indeed, UbcH10 expression is found to be up-regulated in a number of cancer tissues of different origins, and this up-regulation is related with poor prognosis in some cancer types (21)(22)(23)(24)(25). The UBCH10 gene encoding locus 20q13.1 is also reported to be amplified in several tumors (26).…”
mentioning
confidence: 99%